Akt‐mediated phosphorylation of MICU1 regulates mitochondrial Ca2+ levels and tumor growth. (30th November 2018) - Marchi, Saverio; Corricelli, Mariangela; Branchini, Alessio; Vitto, Veronica Angela Maria; Missiroli, Sonia; Morciano, Giampaolo; Perrone, Mariasole; Ferrarese, Mattia; Giorgi, Carlotta; Pinotti, Mirko; Galluzzi, Lorenzo; Kroemer, Guido; et al.
Abstract: Although mitochondria play a multifunctional role in cancer progression and Ca 2+ signaling is remodeled in a wide variety of tumors, the underlying mechanisms that link mitochondrial Ca 2+ homeostasis with malignant tumor formation and growth remain elusive. Here, we show that phosphorylation at the N‐terminal region of the mitochondrial calcium uniporter (MCU) regulatory subunit MICU1 leads to a notable increase in the basal mitochondrial Ca 2+ levels. A pool of active Akt in the mitochondria is responsible for MICU1 phosphorylation, and mitochondrion‐targeted Akt strongly regulates the mitochondrial Ca 2+ content. The Akt‐mediated phosphorylation impairs MICU1 processing and stability, culminating in reactive oxygen species (ROS) production and tumor progression. Thus, our data reveal the crucial role of the Akt‐MICU1 axis in cancer and underscore the strategic importance of the association between aberrant mitochondrial Ca 2+ levels and tumor development. Synopsis: The role of mitochondrial calcium uniporter (MCU) and mitochondrial calcium homeostasis in cancer progression is poorly understood. Active Akt in mitochondria phosphorylates MICU1 to functionally inhibit the MCU complex, thereby increasing basal mitochondrial calcium levels and promoting tumour progression. Akt phosphorylates a serine residue in the N‐terminal region of MICU1. MICU1 phosphorylation increases mitochondrial [Ca 2+ ] at resting conditions. Akt‐mediated phosphorylation affects MICU1 maturation and stability. The Akt‐MICU1 axis plays a critical role in cancer growth by regulating mitochondrial Ca 2+ levels and ROS production. Abstract : Active Akt in mitochondria phosphorylates MICU1 to functionally inhibit the MCU complex, thereby increasing basal mitochondrial calcium levels and promoting tumour progression.